PERAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN USAHA TANI PADI SAWAH DI DESA MARTASARI KECAMATAN PARIGI KABUPATEN PARIGI MAUTONG - Hendra Anggara; Arifuddin Lamusa; Moh Alfit A. Laihi (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
Mertasari Village is one of the villages that have total productivity of 5.9 tons/ha with a harvested area of 117 ha and a production of 687 tons. This study aims to determine the amount of lowland rice farming income and to determine the role of farmer groups in increasing lowland rice farming income in Metasari Village, Parigi District, Parigi Moutong Regency. The research was carried out from November to December 2021 in Mertasari Village, Parigi District, Parigi Moutong Regency, the sampling method used Proportional Stratified Random Sampling by taking 33 respondents from 104 farmers who were members of 3 farmer groups in Mertasari Village. The analytical method used is income analysis. The results showed that the income of paddy farmers, with an average income of Rp. 28.653.174/1.30ha/MT or Rp. 19,102.116/ha/MT. Based on the results of the Chi-Square test on the role of farmer groups in increasing farmers' income, the Chi-Square count value is (6.99). Chi-Square value if the Chi-Square count > Chi-Square table at the significant level (DB; α = 5) and DK = k-1, then Ho is rejected and Ha is accepted from the Chi-Square test results it is known that the role of farmer groups influences the level of rice farming income.